Veno-occlusive Disease in HSCT Patients: Consensus-based Recommendations for Risk Assessment, Diagnosis, and Management by the GITMO Group. Issue 4 (1st December 2020) - Bonifazi, Francesca; Sica, Simona; Angeletti, Alessia; Marktel, Sarah; Prete, Arcangelo; Iori, Anna Paola; Olivari, Diletta; Rossetti, Giulia; Bertaina, Alice; Botti, Stefano; Busca, Alessandro; Carella, Angelo Michele; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Variation in clinical practice affects veno-occlusive disease management, mainly in patients who undergo allogeneic hematopoietic stem cell transplantation. Disputes about diagnostic criteria, treatment, and prophylaxis, due to the lack of high-quality data, are at the base of this variability. With the aim of limiting inconsistency in clinical care, thus improving both patient outcomes and data collection reliability, the Italian Society of Stem cell transplant (Gruppo Italiano Trapianto Midollo Osseo e Terapia Cellulare) launched a collaborative effort to formulate recommendations based on integration of available evidence and expert's consensus. A systematic method, according to US National Institute of Health guidelines and Italian National System for Guidelines, was used. Twenty-nine recommendations were approved with a strong (20) or weak (9) level of agreement, while 26 were rejected. In particular, the panel pointed out the need to achieve an early diagnosis, encouraging the adoption of European Society for Blood and Marrow Transplantation criteria and the prompt use of ultrasonography. Moreover, our experts strongly recommended in favor of prophylactic use of ursodeoxycholic acid. As soon as a veno-occlusive disease diagnosis is established, treatment with defibrotide should be started for at least 21 days. A number of areas of uncertainty, particularly concerning risk stratification and use of diagnostic tools such as elastography has been identified and discussed.